Development of MSMEs' potential through digital marketing in Pabean Udik Village, Indramayu Regency - Bambang Saras Yulistiawan; Rio Wirawan; Catur Nugrahaeni; Andhika Octa Indarso (Community Empowerment, 2022)
Development of digital marketing techniques is mostly driven by changes in customer behavior and technology advancements. A major element of this transformation is the MSME sector. The Faculty of Computer Science, UPN Veteran Jakarta provides community service by training and implementing digital marketing for MSMEs in Pabean Udik Village. This program was carried out to support MSMEs so they can take advantage of digital technology to promote products, effectively interact and communicate with potential customers wherever they are. The program method involves training participants on how to digitize products using their personal smartphones, which is followed by the development of a company profile that serves as a landing page for customers using the Google My Business program. A technical team and trainers help them develop business profiles and upload images of their products. The training has increased the participants' knowledge of product digitization. Additionally, MSME products are eye-catching and simple to market online using Google My Business applications.